Contextual factors, management accounting systems design and managerial performance: evidence from Egyptian hospitals / Salah Abd El Fattah Zaki Hammad - Salah, Abd El Fattah Zaki Hammad (2012)
This study was conducted within the health care industry to investigate the relationship between contingent variables, management accounting systems (MAS) information, and managerial performance. The proposed research framework utilizes the foundations of contingency and work performance theory to determine the contingent variables that influence the extent of use of MAS information; namely, technology, organizational structure, and perceived environmental uncertainty. In addition, it investigates how the appropriate fit between these contingent variables and MAS information characteristics (scope, timeliness, aggregated, and integrated information), which serve as the mediator, would enhance the managerial performance of Egyptian managers in health care. Finally, it examines the effect of hospital size on the relationship between the research contextual variables, MAS information, and managerial performance. Due to its complexity and continuous inept administration despite years following its reform, the Egyptian hospital industry was chosen as the ideal setting to investigate these relationships. In addition, the data analysis of this study used 200 responses from the managers of departments within Egyptian hospitals. Using partial least squares (PLS), the results reveal that the absence or partial support for the positive relationship between technology and MAS information may give attention to re-organize the Egyptian hospitals to make fit between the two variables. In addition, centralization needs to be deemphasized and greater attention should be given to decentralization instead. Moreover, the cognizance of both the internal and external environment in which Egyptian hospitals operate should be considered in designing MAS. Despite MAS information characteristics, such as broad scope, timeliness, and integrated information may provide motivation for Egyptian managers to enhance their managerial iii performance. The absence of the mediating role of MAS information in Egyptian hospitals explains the resistance within Egyptian hospitals (especially among physicians) against MAS that have been provided during healthcare reform. Therefore, MAS designers and Egyptian policy makers should pay attention to eliminate any constraints that limit the professional power of physicians and decentralize decision making via delegating sufficient authority to lower level managers to influence the design of the accounting systems. Finally, the partial support for the existing positive effect for hospital size provides motivation to determine the appropriate hospital size, for both the private and government sectors, that will gain advantage from using more sophisticated accounting systems.